THE IMPACT OF PROBLEM-BASED LEARNING AUGMENTED WITH HOTS PROBLEMS ON STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITIES - Sulistyawati, Destianti; Hadi, Windia; Hidayat, Angga; Muhammad, Rosida Rakhmawati (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study seeks to determine the impact of the Problem-Based Learning (PBL) model supplemented with higher-order thinking skills (HOTS) problems on the mathematical problem-solving skills of high school students. The research employs a quantitative approach, specifically through adopting a quasi-experimental method with a post-test-only non-equivalent control group design. The participants consist of 72 tenth-grade students, with half (36 students) exposed to the PBL model enriched with HOTS problems, and the other half exposed to the standard PBL model without HOTS problems. A descriptive test comprising five mathematical problem-solving items was administered to measure the impact. This test was rigorously validated by two professors from UHAMKA and further validated by students from another tenth-grade class. The data analysis was conducted using the Non-Parametric Mann-Whitney test. The findings suggest a noteworthy difference in mathematical problem-solving abilities between students instructed using the PBL model integrated with HOTS problems and those who did not.